Gestión administrativa y financiera de las microempresas de servicio del casco comercial de Quevedo y su incidencia en la toma de decisiones, periodo 2010-2012 - López Díaz, Daniel Alberto (2012)
Companies today must generate activities to improve its organizational structure and intensify the administrative system and also the financial system through established procedures in finance, accounting and decision-making process, competitive strategies in a changing economy and globalized ago that the present research is focused on investigating whether micro hull Quevedo commercial activities are present in the administrative and financial aspects to verify their financial position, profitability and development over the competition. In the theoretical framework are vital aspects, these being in different theories which correspond to the appearance authors studied, in terms of administrative and financial underpinning research significantly, this is important for the development of diagnostic respective allowing readers document clear arguments as to the conduct of business in the old micro canton Quevedo, in order to propose mechanisms for solving the problems encountered promoting a powerful tool for resource-poor microentrepreneurs. In the market there are different ways and means of conducting business, the same as going from the empirical method that is preceded by experience in this type of family business, a consolidated structures developed with entrepreneurs and small businesses with technical knowledge of the processes study. Different paradigms administrative employees in the middle there is always the prospect that this business has little time to market, absorbed by unfair competition from big business trying   financial institutions as these businesses considered highly risky, more expensive the product of these companies, leaving to this consumer loans that have a high financial cost, leaving small profit margin, so defense mechanisms should be established to strengthen management administrative and financial.